Polylactic acid toughened modified composite material and preparation method thereof

By using specific ratio fibers and compounds with flame retardant in polylactic acid, the problem of insufficient toughness and flame retardant performance of fiber-based materials modified polylactic acid composite materials is solved, and the high toughness of the material is achieved. Excellent compatibility, suitable for a variety of high stress scenarios.

CN119286213APending Publication Date: 2025-01-10LONGDU CHEMICAL NEW MATERIALS LABORATORY +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411599998.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing fiber-based modified polylactic acid composites have limited toughness, poor flame retardant properties and poor material compatibility, which limits their application in high stress scenarios.

Method used

Using specific ratios of polyacrylonitrile-based carbon fiber, glass fiber, wollastonite, dibutyl phthalate, sodium polyacrylate and lauryl methacrylate with polylactic acid, combined with additive flame retardant, Improve the toughness and compatibility of the material and enhance flame retardant performance.

Benefits of technology

It significantly improves the toughness and flame retardant properties of polylactic acid materials, avoids surface layering or peeling during processing, and achieves excellent compatibility and flexible flame retardant performance adjustment. It is suitable for automobile manufacturing, aerospace, electronics Equipment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128029800000021
    Figure BDA0005128029800000021
  • Figure BDA0005128029800000031
    Figure BDA0005128029800000031
  • Figure BDA0005128029800000032
    Figure BDA0005128029800000032
Patent Text Reader

Abstract

The invention provides a polylactic acid toughened modified composite material and a preparation method thereof, and belongs to the technical field of new materials. According to the invention, polyacrylonitrile-based carbon fiber, glass fiber, wollastonite, dibutyl phthalate, sodium polyacrylate and lauryl methacrylate in a specific ratio are adopted as a modified composite material, and the modified composite material and polylactic acid are subjected to melt blending under specific conditions to realize toughening modification of a polylactic acid material; the problems that in the prior art, a fiber material modified polylactic acid composite material is limited in toughness, poor in flame retardant property, poor in material compatibility, limited in flame retardant adding and the like are solved. The polylactic acid toughened and modified composite material prepared by the invention can obviously improve the toughness of the material, avoids the phenomena of surface layering or peeling and the like during the processes of injection molding, extrusion and the like in the subsequent processing of the product, has excellent compatibility, and can be suitable for subsequent addition of various flame retardants with limited compatibility, such as flame retardants, flame retardants, flame retardants, flame retardants, flame retardants, flame retardants, flame retardants, flame retardants, flame retardants, flame retardants and flame retardants. And the flame retardant properties of the product in different purposes can be flexibly adjusted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a polylactic acid toughened and modified composite material and a preparation method thereof. Background Art

[0002] Polylactic acid (PLA) is a high molecular polymer made from green plants. It is made by decomposing the raw materials into glucose, fermenting them to generate lactic acid, and polymerizing the lactic acid. Its physical and chemical properties are similar to those of traditional thermoplastics. However, compared with traditional plastics, it has better biodegradability and will not cause pollution and damage to the environment, solving the energy consumption and environmental pollution problems caused by the processing of traditional plastics.

[0003] In addition to its excellent biodegradability, PLA's good processability and good mechanical properties have led to its extensive research and application. In the biomedical field, PLA can be used to produce disposable medical tools, which can reduce environmental pollution after disposal. Because of its certain biocompatibility and mechanical strength, it can be used to manufacture non-removable surgical sutures and artificial bone tissue. However, PLA materials have problems such as high brittleness, poor toughness, lack of elasticity, general fluidity and slow degradation. These defects limit many industrial applications of PLA, especially industrial and medical applications that require good plastic deformation capabilities under high stress levels. Therefore, in order to further broaden the scope of application of PLA, it is necessary to perform appropriate physical or chemical modifications on it so that it can meet different usage requirements.

[0004] Blending is a common method for polymer modification, which is simple, low-cost and easy to operate. Blending modification of polylactic acid can make PLA obtain relatively ideal comprehensive properties and greatly broaden the application range of polylactic acid. In the prior art, various fiber materials have been disclosed for PLA modification, such as:

[0005] Chinese patent CN107011640B discloses a cellulose toughened modified polylactic acid composite material, which is prepared from 80-100 parts by mass of polylactic acid and 1-20 parts by mass of modified cellulose. After polylactic acid and cellulose modified with diphenylmethane diisocyanate are fully blended on an internal mixer, the blend is taken out and crushed with a pulverizer, and injection molding is performed on an injection molding machine to obtain a modified cellulose toughened polylactic acid composite material. The invention uses one or more of the biodegradable celluloses to blend with polylactic acid, which not only retains the biodegradability of the polylactic acid composite material that can be completely degraded, but also makes the polylactic acid mixed with the modified cellulose have a significant toughening effect, which has made great progress in the study of the brittle weaknesses of polylactic acid.

[0006] Chinese patent CN108239380A discloses a corn straw cellulose toughened modified polylactic acid composite material and its preparation method, which belongs to the field of chemical industry. It is made of the following raw materials by mass: polylactic acid 70% to 95%; modified straw cellulose 5% to 30%. The modified straw cellulose is dissolved in N, N-dimethylacetamide, and the reactor is preheated to 80℃ to 90℃ for 30 to 40min; the homogenizer is turned on, the speed is set to 80 to 120r / min, polylactic acid is added, and the reaction is maintained at 80℃ to 90℃ and 80 to 120r / min for 140 to 160min. After that, the blended solution is uniform, vacuum degassed, and evenly coated by casting method, and dried. The advantages are: the modified straw cellulose is mixed and filled with polylactic acid composite materials. In the mixed and filled composite materials, the modified straw fibers are used to give full play to the reinforcing effect of the straw fibers on the polylactic acid matrix and reduce costs. Among them, 20% solid acid modified straw cellulose has good effects in strength and heat resistance.

[0007] However, the fiber-based material modified polylactic acid composite materials in the prior art have problems such as limited toughness, poor flame retardant properties, and poor material compatibility that limits the addition of flame retardants. Summary of the invention

[0008] The purpose of the present invention is to provide a polylactic acid toughened modified composite material and a preparation method thereof, which not only has excellent flame retardant properties, but also has excellent compatibility and contains a variety of flame retardants to improve the flame retardant properties of the product in different scenarios.

[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0010] The present invention provides a polylactic acid toughened and modified composite material, which is made of the following raw materials in parts by weight:

[0011]

[0012]

[0013] Preferably, it is made from the following raw materials in parts by weight:

[0014] Preferably, the raw material also includes a flame retardant.

[0015] Preferably, the weight proportion of the flame retardant is 3 to 8 parts. Preferably, the flame retardant is an additive flame retardant.

[0016] Preferably, the additive flame retardant is selected from one or more of phosphorus flame retardants, bromine flame retardants, nitrogen flame retardants, nitrogen flame retardants, halogen flame retardants, silicon flame retardants, halogen-free low-smoke flame retardants or composite phosphorus flame retardants.

[0017] The present invention also provides a method for preparing the polylactic acid toughened and modified composite material, comprising the following steps:

[0018] All materials are melt blended to obtain a polylactic acid toughened and modified composite material.

[0019] Preferably, the temperature of the melt blending is 170-190°C.

[0020] Preferably, the melt blending process is performed for 20 to 40 minutes;

[0021] And / or, the rotation speed of the melt blending method is 20 to 40 rpm.

[0022] The present invention also provides the use of the above-mentioned polylactic acid toughened modified composite material, or the polylactic acid toughened modified composite material prepared by the above-mentioned preparation method in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.

[0023] Technical effects and advantages of the present invention:

[0024] The present invention adopts polyacrylonitrile-based carbon fiber, glass fiber, wollastonite, dibutyl phthalate, sodium polyacrylate and lauryl methacrylate in a specific ratio as a modified composite material, and achieves toughening modification of polylactic acid material by melt blending with polylactic acid under specific conditions. The polylactic acid toughening and modified composite material prepared by the present invention can significantly improve the toughness of the material, avoid surface stratification or peeling when the product is subsequently processed through injection molding, extrusion and other processes, and the material has excellent compatibility, and can be suitable for the subsequent addition of a variety of flame retardants with limited compatibility, and flexibly adjust the flame retardant properties of the product in different uses. DETAILED DESCRIPTION

[0025] The present invention provides a polylactic acid toughened and modified composite material, which is made of the following raw materials in parts by weight:

[0026]

[0027] It is preferably made from the following raw materials in parts by weight:

[0028]

[0029] In the present invention, the polylactic acid, also known as polylactide / PLA, is a polyester polymer obtained by polymerization with lactic acid as the main raw material. It is a new type of biodegradable material with good solvent resistance and can be processed in a variety of ways, such as extrusion, spinning, biaxial stretching, and injection blow molding. In addition to being biodegradable, the products made of polylactic acid have good biocompatibility, gloss, transparency, feel and heat resistance. The polylactic acid used in the embodiment of the present invention is white particles with a density of 1.24g / cm 3 , purchased from Nature Works, USA, 4032D.

[0030] In the present invention, the polyacrylonitrile-based carbon fiber is a fibrous carbon material obtained by pre-oxidizing and stabilizing polyacrylonitrile (PAN) fibers at 200-300°C while applying tension and stretching in air, and then carbonizing and heat treating in an inert gas. The fibrous carbon material has a series of advantages such as light weight, high strength, high modulus, chemical corrosion resistance, and small thermal expansion coefficient: 1. It has high specific strength and specific modulus, which is more than 7 times higher than the specific strength of most metals, and the specific modulus is more than 5 times that of metals. Due to this advantage, its composite material can be used in aerospace, automobile industry, sports equipment, etc. 2. The thermal expansion coefficient is smaller than that of most carbon fibers, and the expansion coefficient of the composite material made of it is naturally more stable, and can be used as a standard weighing instrument. 3. The thermal conductivity is close to that of steel. By utilizing this advantage, it can be used as a solar collector material and a heat-conducting shell material with uniform heat transfer. 4. It has good chemical corrosion resistance. Except for strong oxidizing acids, it is very stable to acids, alkalis and organic chemicals, and can be made into various chemical anti-corrosion products. 5. It has excellent wear resistance and can be used as a high-grade friction material. 6. Fatigue strength. The composite material prepared by the composite material still retains a relatively high strength after millions of cycles of stress fatigue tests. The polyacrylonitrile-based carbon fiber powder in the embodiment of the present invention was purchased from Lianyungang Rui Innovation Materials Technology Co., Ltd.

[0031] In the present invention, the glass fiber (Fiberglass) is an inorganic non-metallic material with excellent performance, a wide variety, and the advantages are good insulation, strong heat resistance, good corrosion resistance, and high mechanical strength, but the disadvantages are brittleness and poor wear resistance. It is made of six kinds of ores, namely, pyrophyllite, quartz sand, limestone, dolomite, colemanite, and magnesia stone, through high-temperature melting, wire drawing, winding, weaving and other processes. The diameter of its monofilament is several microns to more than twenty microns, which is equivalent to 1 / 20-1 / 5 of a hair. Each bundle of fiber strands is composed of hundreds or even thousands of monofilaments, and is usually used as reinforcing materials in composite materials, electrical insulation materials and thermal insulation materials, circuit substrates and other fields; the alkali-resistant glass fiber used in the embodiment of the present invention has a specification of 6mm and a tensile strength of 1700Mpa, and is purchased from Taian Haoda New Materials Co., Ltd.

[0032] The weight percentage range of the fiber components of the present invention is the optimal choice. Adding too much or too little fiber components cannot achieve excellent mechanical properties.

[0033] In the present invention, the wollastonite belongs to a single-chain silicate mineral, triclinic system, usually in the form of lamellar, radial or fibrous aggregates. White with a slight gray tint. Glass luster, pearly luster on the cleavage surface. Hardness 4.5-5.0. Density 2.78-2.91 g / cm3. It is mainly produced in the contact metamorphic zone between acidic intrusive rocks and limestones, and is the main mineral component of skarn. In addition, it is also found in some deep metamorphic rocks. It is used as raw material or filler for papermaking, ceramics, cement, rubber, plastics, etc.; gas filter materials and thermal insulation materials; flux for metallurgy, etc. The wollastonite used in the embodiment of the present invention is in powder form, the main component of which is CaSiO3, and the density is 2.85 g / cm 3 , particle size 12 μm, purchased from Yichun Xintuo New Materials Co., Ltd.

[0034] In the present invention, dibutyl phthalate (DBP) is an organic compound with a chemical formula of C 16 H 22 O4 can be used as a plasticizer for polyvinyl acetate, alkyd resin, nitrocellulose, ethyl cellulose, chloroprene rubber and nitrile rubber. The DBP used in the embodiment of the present invention is industrial grade and purchased from the market.

[0035] In the present invention, the chemical formula of the sodium polyacrylate (PAAS) is (C3H3NaO2) n It is a new functional polymer material and an important chemical product. The solid product is a white or light yellow block or powder, and the liquid product is a colorless or light yellow viscous liquid. It is obtained by polymerization of acrylic acid and its esters as raw materials through aqueous solution. It is tasteless, soluble in sodium hydroxide aqueous solution, and precipitated in aqueous solutions such as calcium hydroxide and magnesium hydroxide. Sodium polyacrylate also has strong water absorption. The water absorption rate (pure water) of conventional sodium polyacrylate is hundreds of times that of itself. It is often used as a water treatment agent, brine refining and latex thickening, and can also be used as food thickening and emulsification. Sodium polyacrylate is extremely hygroscopic and is a polymer compound with both hydrophilic and hydrophobic groups. It can slowly dissolve in water to form an extremely viscous transparent liquid, and the viscosity of a 0.5% solution is about 1 Pa·s. The PAAS used in the embodiment of the present invention is an industrial-grade powder purchased from the market.

[0036] In the present invention, the lauryl methacrylate is a polymer chemical raw material with a molecular formula of C16H30O2 and a boiling point of 160°C. The lauryl methacrylate used in the embodiment of the present invention has a CAS number of 142-90-5 and is purchased from Shandong Guohua Chemical Co., Ltd. The relevant experiments were carried out under the laboratory safety supervision and management regulations.

[0037] In the present invention, the raw material also preferably includes a flame retardant; preferably, the weight portion of the flame retardant is 3 to 8 parts; preferably, the flame retardant is an additive flame retardant; preferably, the additive flame retardant is selected from one or more of phosphorus flame retardants, bromine flame retardants, nitrogen flame retardants, nitrogen flame retardants, halogen flame retardants, silicon flame retardants, halogen-free low-smoke flame retardants or composite phosphorus flame retardants; the bromine flame retardants listed in the present invention: such as tetrabromobisphenol A, decabromodiphenyl ether, etc., have high flame retardant efficiency; phosphorus nitrogen flame retardants: have good thermal stability and flame retardant effect; nitrogen flame retardants: are usually used for flame retardant of plastics and textiles; Halogen flame retardants: such as antimony trioxide, magnesium hydroxide, aluminum hydroxide, etc., have good thermal stability and flame retardant effect; silicon flame retardants: such as silica gel, have good thermal stability and flame retardant effect; other types: halogen-free low-smoke flame retardants: such as tetrabromobisphenol A, decabromodiphenyl ether, etc., have lower smoke and toxicity; composite phosphorus flame retardants: such as FR-P, have higher decomposition temperature and better flame retardant effect. In a specific embodiment of the present invention, the K-608 phosphorus series added halogen-free flame retardant used is k-800 colorless transparent oily liquid with a viscosity of 14mpa.s (20°C), purchased from Suzhou Jiayi Chemical Co., Ltd.

[0038] The present invention also provides a method for preparing the polylactic acid toughened and modified composite material, comprising the following steps:

[0039] All materials are melt blended to obtain a polylactic acid toughened and modified composite material.

[0040] Preferably, the temperature of the melt blending is 170-190°C.

[0041] Preferably, the melt blending process is performed for 20 to 40 minutes;

[0042] And / or, the rotation speed of the melt blending method is 20 to 40 rpm.

[0043] The present invention also provides the use of the above-mentioned polylactic acid toughened modified composite material, or the polylactic acid toughened modified composite material prepared by the above-mentioned preparation method in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.

[0044] The application of the polylactic acid toughened and modified composite material in the automobile manufacturing of the present invention is preferably used to manufacture automobile shells, interior trims, suspension systems, engine parts, front-end modules, instrument panel frames, door modules, etc.

[0045] The application of the polylactic acid toughened modified composite material in aerospace is preferably used to reduce weight, thereby improving fuel efficiency and load capacity, making the aircraft lighter and more efficient, and to improve safety and protect internal electronic components from damage; used to enhance structural strength: the application of toughened plastics in aerospace structural parts, such as aircraft wings, fuselages, etc., can significantly improve the strength and toughness of the structure and reduce the risk of damage caused by external impact.

[0046] The application of the polylactic acid toughened modified composite material in electronic devices is preferably used to enhance the mechanical properties of electronic devices and reduce the risk of damage to the devices when subjected to external force impact, such as mobile phone protective cases and headphone cables, which can effectively buffer the impact force and reduce the damage to the devices caused by falling or collision; used to improve safety and prevent wear and tear; used to extend the service life of electronic devices, effectively protect the internal wires from the influence of the external environment, and ensure the long-term stability and safety of the equipment

[0047] The application of the polylactic acid toughened and modified composite material of the present invention in the manufacture of industrial appliances is preferably to increase the environmental performance and service life of the appliances.

[0048] The application of the polylactic acid toughened modified composite material in the manufacture of packaging materials is preferably to improve brittleness: significantly reduce the brittleness of the packaging material, so that it is not easy to break during transportation and storage, and extend the service life; improve impact resistance: when subjected to external force impact, it can absorb more energy to prevent the packaging material from breaking and protect the internal items from damage; enhance durability: the packaging material can still maintain good physical properties after repeated use, reduce the frequency of replacement, and reduce the overall cost; improve safety: it is not easy to break when impacted, reducing the safety hazards caused by the rupture of the packaging material and ensuring the safety of users.

[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] Example 1

[0051]

[0052] In this embodiment, the flame retardant is K-608 phosphorus series added halogen-free flame retardant.

[0053] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0054] The blended material was transferred to a single-screw extruder for extrusion molding, and the thickness was set to 1 mm, and used as a sample for performance testing.

[0055] Example 2

[0056]

[0057] In this embodiment, the flame retardant is MCA flame retardant.

[0058] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0059] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.

[0060] Example 3

[0061]

[0062] In this embodiment, the flame retardant is aluminum hydroxide.

[0063] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0064] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.

[0065] Example 4

[0066]

[0067] In this embodiment, the flame retardant is K-608 phosphorus series added halogen-free flame retardant.

[0068] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0069] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.

[0070] Example 5

[0071]

[0072] In this embodiment, the flame retardant is K-608 phosphorus series added halogen-free flame retardant.

[0073] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0074] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.

[0075] Comparative Example 1

[0076]

[0077] In this embodiment, the flame retardant is K-608 phosphorus series added halogen-free flame retardant.

[0078] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0079] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.

[0080] Comparative Example 2

[0081]

[0082] In this embodiment, the flame retardant is K-608 phosphorus series added halogen-free flame retardant.

[0083] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 150° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0084] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.

[0085] Comparative Example 3

[0086]

[0087]

[0088] In this embodiment, the flame retardant is K-608 phosphorus series added halogen-free flame retardant.

[0089] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0090] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.

[0091] Comparative Example 4

[0092]

[0093] In this embodiment, the flame retardant is K-608 phosphorus series added halogen-free flame retardant.

[0094] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0095] The blended material was transferred to a single-screw extruder for extrusion molding, and the thickness was set to 1 mm, and used as a sample for performance testing.

[0096] Comparative Example 5

[0097]

[0098]

[0099] In this embodiment, the flame retardant is K-608 phosphorus series added halogen-free flame retardant.

[0100] All raw materials were put into an internal mixer for melt blending at a speed of 30 rpm and a temperature of 180° C. for 30 min to obtain a polylactic acid toughened and modified composite material.

[0101] The blended material was transferred to a single-screw extruder for extrusion molding, and the thickness was set to 1 mm, and used as a sample for performance testing.

[0102] Experimental example

[0103] After the blended materials of Examples 1 to 5 and Comparative Examples 1 to 5 were transferred to a single screw extruder for extrusion molding, the apparent properties of the samples were recorded. The results are shown in Table 1 below:

[0104] Table 1 Record results of apparent properties of extruded samples

[0105]

[0106] The results of the apparent properties indicate that the blended materials and processing parameters provided in the embodiments of the present invention can obtain products with optimal compatibility and stability.

[0107] The following tests were performed using pure PLA, materials obtained in Examples 1 to 5, and Comparative Examples 1 to 5 as samples:

[0108] Mechanical properties test:

[0109] Use a universal mechanical properties tester to test the tensile properties of the specimens and record the results;

[0110] The sample size is 4mm×1mm, the chuck spacing is 30mm, and the tensile speed is 10mm / min.

[0111] The samples were placed at room temperature for 48 hours before testing.

[0112] The tensile elastic modulus is tested during the tensile test. During the elastic deformation stage of the tensile test, the strain value of the sample under a specific stress is measured and the tensile elastic modulus is calculated using Hooke's law:

[0113] E = σ / ε, where E is the tensile elastic modulus, σ is stress, and ε is strain

[0114] The measurement results are shown in Table 2 below:

[0115] Table 2 Mechanical properties test results

[0116]

[0117] From the mechanical property test results, it can be seen that the polylactic acid toughened modified composite material provided by the present invention can increase the elongation at break from 6.61% of pure PLA to 60.66%-71.04%; the tensile strength is increased from 54.11MPa of pure PLA to 90.13MPa-102.53MPa; the tensile elastic modulus is increased from 3.55GPa of pure PLA to 0.58GPa-0.71GPa, indicating that it has the excellent performance of not being easy to break or fracture when subjected to impact or pressure, and has good application prospects in the industry; and the test results also reflect that the selection of each raw material in the blend and the setting of the addition amount have an important influence on the toughening effect, and the use of the formula in the embodiment of the present invention can make the blend play a better compatibility and interaction, thereby obtaining the optimal performance.

[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polylactic acid toughened and modified composite material, characterized in that: Made from the following raw materials in parts by weight:

2. The polylactic acid toughened and modified composite material according to claim 1, characterized in that: Made from the following raw materials in parts by weight:

3. The polylactic acid toughened and modified composite material according to claim 1 or 2, characterized in that: The raw materials also include a flame retardant.

4. The polylactic acid toughened and modified composite material according to claim 3, characterized in that: The weight proportion of the flame retardant is 3 to 8 parts.

5. The polylactic acid toughened and modified composite material according to claim 3, characterized in that: The flame retardant is an additive flame retardant.

6. The polylactic acid toughened and modified composite material according to claim 5, characterized in that: The additive flame retardant is selected from one or more of phosphorus flame retardants, bromine flame retardants, nitrogen flame retardants, nitrogen flame retardants, halogen flame retardants, silicon flame retardants, halogen-free low-smoke flame retardants or composite phosphorus flame retardants.

7. The method for preparing the polylactic acid toughened and modified composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: All materials are melt blended to obtain a polylactic acid toughened and modified composite material.

8. The preparation method according to claim 7, characterized in that: The temperature of the melt blending is 170-190°C.

9. The preparation method according to claim 7, characterized in that: The time of the melt blending method is 20 to 40 minutes; And / or, the rotation speed of the melt blending method is 20 to 40 rpm.

10. Use of the polylactic acid toughened and modified composite material according to any one of claims 1 to 6, or the polylactic acid toughened and modified composite material prepared by the preparation method according to any one of claims 7 to 9 in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.

Citation Information

Patent Citations

  • A cellulose-toughened modified polylactic acid composite material and its preparation method

    CN107011640B

  • Polylactic acid composite material which is toughened and modified by corn straw cellulose and preparation method of polylactic acid composite material

    CN108239380A

  • High strength and high heat resistance polylactic acid composite material and preparation method thereof

    CN101962468A

  • Degradable engineering plastic and preparation method thereof

    CN102276964A

  • High-performance flame-retardant PLA (polylactic acid) / graphene nano-sheet composite material and preparation method thereof

    CN103772926A